Topical Dosage for Treatment of ChemotherapyInduced Peripheral Neuropathy - Sengar, Vaishali; Kumar Jain, Upendra (International Journal of Psychosocial Rehabilitation, 2019)
Peripheral neuropathy caused by chemotherapy is a general therapeutic limiting factor that greatly affects patients ' daily lives, mostly due to lack of appropriate palliative options. CIPN is a severe, often chronic condition with pain and reduced function. In addition, CIPN is its most common dose-limiting side effect, which is decreasing and could affect treatment outcomes. Interestingly, the incidence of paclitaxel (taxane) induced peripheral neuropathy is very high ranging from 53-83% with severity in 2-33% patients. The clinical symptoms of CIPN affect sensory, motor and sometimes autonomic functions. A sensory disturbance includes allodynia, hyperalgesia and spontaneous sensations such as tingling, burning, electric, stabbing, numbness, and prickling. Hence, considering the drawbacks of existing treatments, this study provides a topical gel comprising of pharmacological agents with multiple mechanisms of action and regeneration of damaged nerve fibres. The formulated gel successfully qualified the tests for semi-solid dosage form such as color, appearance, and homogeneity, measurement of pH, viscosity, spreadability, drug content and stability.